Effect of Different Mesostructured Material Based On Silica (Tio2, Sba-15 And Cab-O-Sil) As Cobalt Supports For Fischer-Tropsch Synthesis - Mohamad Irsyad, Mohamad Mazuki (2012)
The research was about the synthesis of active and selective for syngas processing via Fischer–Tropsch synthesis (FTS) producing clean and best fuel. A series of 20 wt. % cobalt catalysts be prepared by impregnation of a mesoporous molecular sieve based on silica as 75 wt. % of cobalt catalytic supporters (SBA-15, TiO and CabO-Sil) with 5 wt. % Zn promoter for comparison purposes. All materials used characterizing by several analysis equipments which are SEM, TGA and FTIR. The characterization results achieve gave a great influence of mesoporous support porosity on the structure, reducibility of cobalt oxide species supported over the selected materials. Firstly, the experiment was started from the synthesis of SBA-15. TiO2 and Cab-O-Sil are commercialized support. Then, the silica as cobalt supporters were synthesized by incipient wetness impregnation method of using mixture of Cobalt (II) Nitrate and Zinc Nitrate Hexahydrate solution. Next, the prepared catalysts were calcined at 350°C for 6 h by increasing the temperature at a controlled heating rate of 2°C/min. The characterization of catalysts and catalyst studies was performed. The result from experiment was SBA-15 supporter shown the better result compared to other samples as the microscopic size captured by SEM equipment prove that SBA-15 had smoothest and smallest of mesoporous surface size. The result from FTIR showed that the peak at around 3,440 cm-1 have the hydroxyl groups and about 1,630 cm -12 is due to the bending vibrations of O-H bonds that the percentage reflectance of O-H bonds which indicates the SBA-15 can effectively restrain the loss of surface hydroxyl groups during calcinations. The peak around 1000-1200 cm1 can be assigned to the siloxane or Si-O-Si stretching bands; peak appears as a broad and strong peaking the sample. Lastly, TGA result showed that SBA-15 can help the catalyst samples restrained more water content in the evaporation process and had high thermal stability that can prolong life at high temperature and high pressure in the Fischer-Tropsch synthesis. The new silica as cobalt supporter will be developed to enhance the performance of the best and clean fuel production. This research hopefully can be carried out successful in order to get the new invention for production of catalyst that will produce the best and clean fuel and to get rid of exceed cost of production but in the same quality of expensive product.